CMR parameters and CMR-FT in repaired tetralogy of Fallot - Rana A. Attalla (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Repaired tetralogy of Fallot patients develops postoperative complications that are in need for follow-up and re-intervention in some circumstances. CMR myocardial feature tracking is a novel method that allows quantification of bi-atrial and bi-ventricular mechanics of deformation. So our aim is to assess the added value of cardiac magnetic resonance imaging and its advanced feature tracking analysis in evaluation of repaired tetralogy of Fallot patients. Results CMR was done with feature tracking post-processing analysis for 56 patients with repaired tetralogy of Fallot and 56 healthy volunteers. The commonest postoperative complications in patients with repaired tetralogy of Fallot are in the following order: pulmonary regurgitation with subsequent right ventricular dilatation and tricuspid regurgitation followed by pulmonary stenosis, right ventricular dysfunction, right ventricular outflow tract dilatation, left ventricular dysfunction, aortic and mitral regurgitation and residual ventricular septal defect. All right ventricular volumes were found to be significantly increased compared to those of the healthy volunteers (p value < 0.001) also left ventricular end-diastolic and end-systolic volumes indexed were found to be increased in those patients compared to healthy volunteers (p value < 0.001). Right and left ventricular function were significantly lower in those patients compared to controls. Bi-ventricular CMR-FT indices and right atrial global longitudinal strain were found to be significantly lower in patients with repaired tetralogy of Fallot compared to controls. Right atrium global longitudinal strain was found to be significantly correlated with right ventricular global longitudinal strain and did not correlate with right ventricular ejection fraction and end-diastolic volume indexed; p value < 0.001, 0.109 and 0.565, respectively. Right ventricular global circumferential strain was found to be significantly increased in patients with right ventricular outflow tract obstruction compared to those without obstruction (− 16.26 ± 4.27% vs. − 12.2 ± 3.78%, respectively). Pulmonary regurgitant volume indexed was found to be significantly related to right ventricle longitudinal strain (p value 0.027). Conclusion Biventricular volumetric measures are increased in patients with repaired tetralogy of Fallot compared to controls; however, feature tracking parameters for both ventricles and right atrium are lower in those patients compared to controls.